Power Systems and Smart Energies - Derbel, Faouzi; Derbel, Nabil; Kanoun, Olfa (Advances in Systems, Signals and Devices ;, 2017)
Power Systems & Smart Energies (PSE) is dedicated to the design, modeling, exploitation and diagnostics of electrical power systems and renewable energy sources. It covers topics in the area of power electrical engineering including, power electronic systems, power electronic converters, electrical machine design, monitoring and diagnostics, renewable energy systems, automotive power systems, smart grids, and distribution networks.